(untitled) (Ius Novum, 2023)
The article is of scientific research nature and it aims to analyse resolutions and rulings of the Supreme Court Criminal Chamber concerning substantive criminal law passed in 2022 as a response to the so-called legal questions. The subject of the analysis covers such issues as: the crime of failure to report a crime (Article 240 § 1 of the Criminal Code); suspension of the statute of limitations for criminal offenses due to the Covid-19 pandemic; a student of the Faculty of Public Order of the Academy of Internal Affairs in Szczytno as a person not serving in the state security bodies; and revocation of a driving licence in the event its holder who is a member of a military unit performing tasks outside the country commits an act consisting in driving a motor vehicle under the influence of alcohol (Article 135(1) of the Road Traffic Act). The basic scientific research aim is to evaluate the legitimacy of this body’s interpretation of the regulations covering the legal issues referred to the Supreme Court for resolution. The main research theses consist in showing that the so-called legal questions referred to the Supreme Court play an important role in ensuring the uniformity of common and military courts’ judgements because the body’s stance is based on in-depth reasoning. The research findings are original in nature as they creatively develop the interpretation contained in the resolutions analysed. The research is mainly national in scope. The article is especially important for science because it contains a deepened dogmatic analysis and a big load of theoretical thought, as well as it is practically useful as it enriches the Supreme Court’s arguments or refers to circumstances justifying different opinions.